Combination of generalized-ensemble algorithms and one-dimensional reference interaction site model theory - Mitsutake, A.; Kinoshita, M.; Hirata, F.; Okamoto, Y. (Condensed Matter Physics, 2007)
The article reports an attempt to study the protein folding problem by generalized-ensemble Monte Carlo simulations with reference interaction site model theory. Generalized-ensemble algorithms greatly enhance the configurational space sampling in computer simulations. The reference interaction site model theory treats solvent effects with solvent molecular shape and estimate solvation free energy around proteins. We have developed simulation algorithms which combine generalized-ensemble algorithms and one-dimensional reference interaction site model theory. This treatment can also use a simulation with three-dimensional reference interaction site model theory. In this review, we describe the methods and present the results of these simulations for a peptide.